2015
DOI: 10.3390/molecules201219791
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Fermentation Treatments on Wine Volatile and Sensory Profile of the New Disease Tolerant Cultivar Solaris

Abstract: Solaris is a new disease tolerant cultivar increasingly cultivated in cool climate regions. In order to explore the winemaking processes' potential to make different styles of Solaris wines, the effects of different pre-fermentation treatments (direct press after crushing, whole cluster press, cold maceration, and skin fermentation) on the volatile profile, chemical, and sensory properties of Solaris wines were investigated. Cold maceration treatment for 24 h and fermentation on skin led to wines with lower ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 59 publications
7
59
0
1
Order By: Relevance
“…Additionally, linalool level in SFB wine was also significantly higher than that of control wine ( P < 0.05) (Table ). These compounds have been described by terms such as lychee, citrus, lavender, citronella, rose, sweet, floral, tropical fruit, peach, honey and Muscat (Aleixandre‐Tudo et al ., ; Zhang et al ., ). Research by Komes et al .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Additionally, linalool level in SFB wine was also significantly higher than that of control wine ( P < 0.05) (Table ). These compounds have been described by terms such as lychee, citrus, lavender, citronella, rose, sweet, floral, tropical fruit, peach, honey and Muscat (Aleixandre‐Tudo et al ., ; Zhang et al ., ). Research by Komes et al .…”
Section: Resultsmentioning
confidence: 97%
“…() showed that terpenes were scarcely affected by alcoholic fermentation process, and furthermore, the presence of the skins during the fermentation process could decrease the levels of terpenes in the finished wines (Selli et al ., ; Rodrıguez‐Bencomo et al ., ). However, our study showed that extended skin contact period caused an increase in citronellol and linalool values, which were in accordance with the previous studies (Aleixandre‐Tudo et al ., ; Zhang et al ., ). Therefore, by extended skin contact period, terpenes, regarded as a typical grape varietal character impacting odorants and discovered mostly in floral varieties, could be more retained in the wines.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations